Children, Art museum, Talking and Asking Questions - Vijitsatitrat, Atipat (DEC Journal : Art and Design, 2024)
The purpose of this article is to point out taking children to learn the modern art in art museums. Talking and asking questions that are critical to the development of the foundations of life, both physically, emotionally, and mentally. The art museum has huge, light spaces. It is ideal for children to learn. Talking and asking questions are important to give children an understanding of the artwork. The artist’s ideas. The talk and questions will depend on the age of the child to be used properly so that the child can learn the linkage of the work to themself.